2015
DOI: 10.1159/000440817
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Surgical Staplers: Does Staple Direction Affect the Strength of the Anastomosis?

Abstract: Background: Few studies have been conducted regarding the optimal staple direction in gastrointestinal anastomosis. The purpose of this study was to evaluate the burst pressure of the anastomosis depending on the firing direction of the stapler. Methods: Pig esophagus and small bowel were used for all experiments. The small intestine represented a thin intestinal tract and the esophagus represented a thick intestinal tract. A side-to-side anastomosis was performed using a linear stapler, and the burst pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…described a similar experiment on porcine oesophagojejunostomy models using open surgical staplers. [ 22 ] The authors of this study had concluded that firing the surgical stapler from the thinner side, i.e., the small bowel, is better as it yielded higher BP on testing. This was in contradiction to our experiment where we demonstrated that firing the stapler from the gastric side, i.e., Group mLSA1, yielded higher BP when compared to Group mLSA2.…”
Section: Discussionmentioning
confidence: 99%
“…described a similar experiment on porcine oesophagojejunostomy models using open surgical staplers. [ 22 ] The authors of this study had concluded that firing the surgical stapler from the thinner side, i.e., the small bowel, is better as it yielded higher BP on testing. This was in contradiction to our experiment where we demonstrated that firing the stapler from the gastric side, i.e., Group mLSA1, yielded higher BP when compared to Group mLSA2.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the edematous collagen plates, the compressive pressure curve formed a gradual plateau even after further compression was applied beyond the optimal compression point. If there were presence of edema or inflammation in the colon, the tissue structure could be weakened and its density, elasticity, and restoration capability would have been deteriorated [ 15 ]. As a result, its structural integrity could be even further weakened by the accumulation of muscular and submucosal tears caused by overcompression [ 12 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the burst pressures of anastomoses using magnets were greater than those using a staple line. 11 The extrusion time of the jejunal magnets or polythene tube device from the pylorus was determined according to the peristaltic activity and was also related to the shape and size of the object. Due to its complex structure, the polythene tube device was expelled later than the jejunal magnet.…”
Section: Discussionmentioning
confidence: 99%